2008
DOI: 10.1007/s00264-008-0625-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI in detecting early physeal changes due to acute osteoarticular infection around the knee joint: a pilot study

Abstract: Physeal changes of any aetiology in children are usually diagnosed once the deformity is clinically evident. Between January 2006 and June 2007, 15 children who suffered from acute osteoarticular infection around the knee joint were studied. They were called up for follow-up six months after the onset of infection. All patients were evaluated by clinical and roentgenographic examination before undergoing magnetic resonance imaging (MRI) study of both knees "with the unaffected knee serving as control". Abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…MR imaging can depict the bony bridge as early as 6 months after the infection. Fortunately, many children with physeal involvement show resolution of the physeal insult with adequate antibiotic therapy (64,65). A recently observed phenomenon is the development of pathologic fractures.…”
Section: Review: Hematogenous Osteomyelitis In Infants and Childrenmentioning
confidence: 99%
“…MR imaging can depict the bony bridge as early as 6 months after the infection. Fortunately, many children with physeal involvement show resolution of the physeal insult with adequate antibiotic therapy (64,65). A recently observed phenomenon is the development of pathologic fractures.…”
Section: Review: Hematogenous Osteomyelitis In Infants and Childrenmentioning
confidence: 99%
“…Multiple institutional guidelines have demonstrated that its earlier use remarkably improves the identification of OAIs surgical candidates, thus reducing the rate of sequelae and reoperations ( 1 , 5 , 6 , 12 16 , 20 24 ). Despite its benefits, the awareness of the resource intensity required by MRI has led to the development of multidisciplinary teams, to expedite the discussion around OAIs management among all the implicated stakeholders, such as pediatricians, orthopedic surgeons, anesthesiologists and radiologists ( 15 , 16 , 18 , 20 , 24 26 ).…”
Section: The Difficulty Of Accessing An Emergency Mrimentioning
confidence: 99%
“…Magnetic resonance (MR) imaging is superior to other modalities for detecting early osteomyelitis in people . MR imaging has the advantage of excellent soft‐tissue contrast resolution to visualize the presence of osteomyelitis and its complications, which include soft‐tissue and bone abscesses, physeal involvement, and infectious arthritis .…”
Section: Introductionmentioning
confidence: 99%
“…MR imaging has the advantage of excellent soft‐tissue contrast resolution to visualize the presence of osteomyelitis and its complications, which include soft‐tissue and bone abscesses, physeal involvement, and infectious arthritis . In children, it is used for early detection of osteomyelitis due to infectious arthritis and hematogenous routes of joint infection . Radiography still serves as the initial screening modality in children for osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%